Scientific basis of fat requirement for Indians and recent trends in CVD - Ibrahim, S Ahamed (Indian Journal of Community Health, 2014)
Dietary fats have several roles such as provision of metabolic energy, fat soluble vitamins and essential fatty acids (linoleic, LA and ?-linolenic, ALNA). Fats improve texture and palatability and have a satiety role. LA and ALNA and their long-chain polyunstaturated fatty acids (LC n-6 PUFA and LC n-3 PUFA respectively) are important structural membrane components and therefore essential for formation of new tissues. LC n-3 PUFA have specific role in vision and nervous system. Both n-6 and n-3 PUFA are essential for fetal and early infant growth and development and nervous tissue development. The absolute levels and ratio of n-6 and n-3 PUFA in membrane affect a wide range of physiological processes either directly or through eicosanoids. The individual components of fats affect the risk of diet - related chronic diseases through the atherogenic effects of plasma lipids, insulin resistance, thrombosis, endothelial dysfunction as well as pathways of inflammation. The chain length/geometric configuration of double bonds and position of saturated (SFA), mono unsaturated (MUFA) or PUFA on glycerol backbone (triglyceride structure) modify the nutritional and metabolic effects of dietary fats. The non-glyceride components present in the vegetable oils have hypocholesterolemic and antioxidant effects. Several lines of evidence have documented that restrictions in SFA and cholesterol, negligible intake of trans fatty acids (TFA) on the one hand and preference for more than one type of vegetable oil (to ensure adequate absolute intakes of LA, ALNA and their ratio), adding n-3 PUFA from fish or plant sources, and ensuring moderate intake of total fat in the diet substantially reduces the risk of diet-related chronic diseases. Studies were done at National Institute of Nutrition on intake of individual fatty acids, the pro/anti-athero-thrombogenic effects of different types of visible fats in Indian adults, insulin sensitivity and the antioxidant properties of unique non glyceride components of some of the commonly consumed edible oils. From the data generated, the quantity and combination of visible fats, foods to be preferred so as to increase ‘healthy fats', foods to be avoided/restricted to reduce ‘unhealthy fats' have been worked out. Ensuring optimal intake of fat (quantity and quality) throughout life-span may contribute to the widely prevalent nutrition and health problems in India (low birth weight, chronic energy deficiency and diet-related chronic diseases). The rapid increase in prevalence of diet-related chronic diseases including type 2 diabetes, obesity and hypertension worldwide possess an immense public health and medical challenge for the implementation of successful preventive and treatment strategies. Insulin resistance is an important risk factor for type 2 diabetes and is often associated with other metabolic abnormalities and cardiovascular risk factors. Moreover it is also an important risk factor for cardiovascular diseases (CVD). Obesity when associated with abdominal adiposity is an important determinant of insulin resistance and represents the most important risk factor for type 2 diabetes and metabolic syndrome. The explanation for the explosion of the epidemic of chronic diseases involve changes in dietary habits and or / increasing the sedentary life style, since our genetic pool remained stable. Poor control of the life style risk factors results in metabolic dysregulation, endothelial dysfunction and increased adiposity which in turn together lead to dyslipidemia, hypertension, type 2 diabetes, systemic inflammation, thrombosis and risk of arrhythmia (1). The ultimate result is sub clinical and then clinically apparent CVD including coronary heart disease (CHD), cardiac arrhythmia, heart failure and stroke. The best way of preventing chronic diseases is to take a balanced diet that does not provide excess calories along with regular physical activity. Over the past few decades evidences that has accumulated suggests that both the quality and quantity of dietary fat is associated with pathogenesis of several diet-related chronic diseases (2).